2017
DOI: 10.1021/acs.jpcc.6b10540
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Hydrogen Production of Ta2O5 Nanotubes Decorated with NiO Nanoparticles by Modified Sputtering Deposition

Abstract: The use of metal/oxide nanoparticles (NPs) as cocatalysts in heterogeneous photocatalysis is an important strategy to improve the photocatalytic activity of semiconductors for hydrogen generation. This article reports the use of a modified sputtering deposition method to prepare ultrafine NiO NPs cocatalysts dispersed on anodic Ta2O5 nanotubes (NTs). In situ X-ray absorption near-edge spectroscopy (XANES) measurements revealed that after exposing the as-prepared Ni NPs to air atmosphere a mixture of 68% of Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 60 publications
0
40
0
4
Order By: Relevance
“…Electrochemical anodization in fluorinated electrolytes is one of the most promising and effective methods employed to obtain highly ordered nanotube arrays of TiO 2 and many other materials with controllable morphologies [20][21][22] . Optimizing anodic film topography and its properties are some of the main interests for smart material application 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical anodization in fluorinated electrolytes is one of the most promising and effective methods employed to obtain highly ordered nanotube arrays of TiO 2 and many other materials with controllable morphologies [20][21][22] . Optimizing anodic film topography and its properties are some of the main interests for smart material application 23 .…”
Section: Introductionmentioning
confidence: 99%
“… 40 It is attributed to one mean peak for the O 1s spectrum at 530.1 eV, which is confirmed to the presence of O atoms in the LaNaTaO 3 crystal lattice; besides, there are other two peaks centered at 531.4 and 532.5 eV, leading to the presence of – OH surface and adsorbed O ( Figure 5 d), respectively. 41 The Na 1s peak is located at ∼1071.3 eV, identifying the Na + oxidation state, as obviously seen in Figure 5 e. The XPS results confirmed that the prepared perovskite was composed of Ru 4+ , Na + , La 3+ , Ta 5+ , and oxygen in the crystal lattice, and their atomic percentages were determined to be approximately 0.98, 7.87, 1.98, 70.82, and 19.05%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing concern over the global energy crisis, solar-driven photocatalysis utilizing 1D semiconductors to generate clean chemical fuels such as photocatalytic hydrogen production has been deemed as a promising route to meet the increasing worldwide demands for clean energy [116]. Some typical works on photocatalytic hydrogen production over anodized 1D semiconductors have been extensively reported [143][144][145]. For instance, hierarchical anodized Ta 2 O 5 NTs functionalized with NiO NPs (NiO/Ta 2 O 5 NTs) was prepared by Teixeira's group [143].…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…Some typical works on photocatalytic hydrogen production over anodized 1D semiconductors have been extensively reported [143][144][145]. For instance, hierarchical anodized Ta 2 O 5 NTs functionalized with NiO NPs (NiO/Ta 2 O 5 NTs) was prepared by Teixeira's group [143]. It was significant to reveal that NiO/Ta 2 O 5 NTs nanocomposite exhibited much more enhanced H 2 production rate (figure 20) in comparison with pure Ta 2 O 5 NTs under the same conditions, which results from the synergetic effect of improved separation of electron-hole pairs, increased catalytic active sites and enhanced light absorption afforded by NiO NPs as well as unique hierarchical structure.…”
Section: Hydrogen Productionmentioning
confidence: 99%